2015
DOI: 10.1007/s10620-015-3613-0
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Zinc Deficiency in Patients with Cirrhosis: When Should We Start?

Abstract: Zinc deficiency is highly prevalent in cirrhotic patients with Child-Pugh score B or C, and with MELD score ≥15. Zinc deficiency also correlates with disease severity, infection, and a worse transplant-free survival. Screening for zinc deficiency should be considered in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 29 publications
(19 reference statements)
1
32
0
Order By: Relevance
“…A similar study found that serum zinc level was lowered in those with severe cirrhosis than in those with mild cirrhosis in 163 patients. 7 Further, the concentration of serum zinc level decreased with severity of liver disease and found a significant negative correlation between serum zinc and Child score (p<0.001). 5 Therefore, screening for zinc deficiency in these patients with more advanced cirrhosis seems to be warranted as a marker of advanced liver disease.…”
Section: Hbv+hcv 1%mentioning
confidence: 87%
See 2 more Smart Citations
“…A similar study found that serum zinc level was lowered in those with severe cirrhosis than in those with mild cirrhosis in 163 patients. 7 Further, the concentration of serum zinc level decreased with severity of liver disease and found a significant negative correlation between serum zinc and Child score (p<0.001). 5 Therefore, screening for zinc deficiency in these patients with more advanced cirrhosis seems to be warranted as a marker of advanced liver disease.…”
Section: Hbv+hcv 1%mentioning
confidence: 87%
“…It is consistent with that of other studies which showed most of the cirrhosis of liver occurred in male patients. 7,9,10 This may be due to more exposure of alcohol among male patients. This may be due to increased alcohol consumption among male population in Myanmar and it consequently leads to increased number of male cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, chelating action by L‐dopa used in LCIG treatment is considered to cause zinc deficiency in the cases presented. Comorbidities or underlying conditions that could also cause zinc deficiency include liver disease (Sengupta et al, ), diabetes (Walter et al, ), chronic inflammatory bowel disease (Naber, van den Hamer, Baadenhuysen, & Jansen, ), and renal diseases such as the nephrotic syndrome and malabsorption after the small intestine excision (Makhlough et al, ). The first patient has diabetes mellitus but is unlikely the sole cause for zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Mohammad M. et al, presented the results of the Zinc Supplementation in Alcoholic Cirrhosis (ZAC) trial [62]; which is based on the fact that zinc deficiency occurs in human subjects with alcoholic cirrhosis (AC) [63] and zinc supplementation attenuates liver injury/inflammation in murine models of ALD [64,65]. In this small single center double blind placebo controlled trial, the authors aimed to determine if low dose zinc supplementation (220 mg/day for 3 months) improves serum biomarkers of liver injury/inflammation and clinical status of patients with AC.…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%